STRATEGI PENJADWALAN PERAWATAN SISTEM PENDINGIN PADA KAPAL CARGO 3650 DWT - M Sena Majid; Raden Dimas Endro; Nurvita Arumsari (Proceedings Conference on Marine Engineering and its Application, 2023)
This study aims to enhance the closed cooling system's reliability on the cargo 3650 dwtship by evaluating maintenance schedules. To achieve this, an effective maintenance program isnecessary. The Fault Tree Analysis (FTA) method is used to analyze potential component failures andidentify main causes. A total of 22 components are identified, including Main FW Cooler, AuxiliarySea Water Pump, Turbocharger, and others. All components are assessed to determine critical ones,included in the minimal cut set table, and relationships for a Reliability Block Diagram (RBD).Additionally, distribution types are determined to model time between component failures and predictsystem reliability. Reliability calculations are done for each component, and results measure overallsystem reliability. Turbocharger is the component with the shortest scheduling time, t=1650 hours, areference for maintenance. The final stage involves cost calculations to compare Corrective andPreventive Maintenance. Preventive maintenance analysis improves cost and time efficiency. Thus,implementing a maintenance program based on this research can enhance cooling system reliabilityon the 3650 dwt ship.